Retreatment of XP-endo Shaper and R-Endo files in curved root canals - Hayam Y. Hassan; Fahd M. Hadhoud; Ayman Mandorah (BMC, 2023)
Abstract Objectives To compare the retreatment efficiency of XP-endo Shaper and R-Endo files in curved root canals using ImageJ software. Methods Forty extracted mandibular first molars with curved mesial canals (25°-35°) were chosen. Access cavities, preparation and obturation of root canals were performed. Roots were randomly distributed into two groups corresponding to the retreatment files used. Group 1 retreated with XP-endo Shaper file, and group 2 retreated with R-Endo files. Each root was sectioned and photographed. ImageJ software was used to estimate the percentage of residual filling material that existed on the three root canal segments. Mann-Whitney U and the Kruskal-Wallis tests were used to compare the percentages of residual filling material between the teeth segments (P < .05). Results The R-Endo group showed a significantly higher median percentage of residual filling material than the XP-endo Shaper group. In both groups, the coronal segments had the highest median of the residual filling material, followed by the middle and apical segments. Conclusion XP-endo Shaper is significantly more effective than R-Endo in removing root canal filling materials in the coronal, middle, and apical segments.